Pre-probiotic effects of different bacterial species in aquaculture: behavioral, hematological and oxidative stress responses - Alak Gonca; Kotan Recep; Uçar Arzu; Parlak Veysel; Atamanalp Muhammed (Oceanological and Hydrobiological Studies)
There is very limited aquaculture research on candidate probiotics and their effects on fish physiology. In this study, acute applications of four different molecularly identified bacterial species – Brevibacillus brevis FD-1 (A), Pseudomonas fluorescens FDG-37 (B), Bacillus sphaericus FD-48 (C), and B. amyloliquefaciens TV-17C (D), with potential in aquaculture, were tested in rainbow trout (Oncorhynchus mykiss) under static conditions. Physiological changes in blood tissue [hematological indices: erythrocyte count (RBC), leukocyte count (WBC), hemoglobin (Hb), hematocrit (Hct), platelet count (PLT), mean cell hemoglobin concentration (MCHC), mean cell hemoglobin (MCH), and mean cell volume (MCV)], oxidative stress responses in liver and gill tissues [malondialdehyde (MDA) level, antioxidant enzyme activities: superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX), glutathione reductase (GR), glutathione-S-transferase (GST), glucose-6-phosphate dehydrogenase (G6PD)] and acetylcholinesterase (AChE) activity in brain tissue (as neurotoxic biomarker) were investigated. Additionally, behavioral differences were recorded by measuring swimming performance to support neurotoxic findings in all treatment groups. The LC5024 value of FDG-37 strain was determined through analysis as 1.0 × 108 CFU ml-1. Inhibition of enzyme activity, increase in the MDA level, as well as significant differences in hematological indices and swimming performance were determined in rainbow trout treated with B compared to control and other bacterial groups in gills. The potential for using group FD-48 and TV-17C bacterial strains as probiotics in aquaculture is more pertinent when considering the research findings and water quality parameters.